(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2011)
Well-preserved middle and late Hettangian radiolarians have been discovered S-E of Mt. Camicia (Central Apennines) in limestone beds that contain also Hettangian ammonites. These beds are part of an Upper Triassic to Lower Jurassic carbonate succession, which crops out in the eastern part of the Gran Sasso range. This succession includes euxinic deposits (bituminous dolostone) and other pelagic sediments (mudstone and calcarenites) which developed in a basin rimmed by a carbonate platform. In the same time interval, the well-known formations of Dolomia Principale and Calcare Massiccio were forming on this platform. In this paper we examine the radiolarian assemblages collected in three levels of the ammonite bearing beds, and we define two new genera (Squinabolia and Turritus) and eight new radiolarian species (Anaticapitula parvireticulata, Anaticapitula triangularis, Farcus aquilensis, Farcus leonseveroi, Parahsuum vraddense, Squinabolia multispinata, Turritus venturii, Zhamoidellum sphaericus), and we define twenty four other species, for a total of thirty eight identified species. The ammonites in the lowest level indicate a middle Hettangian age, those from the two upper levels a late Hettangian. In the Western Tethys successions bearing Hettangian radiolarians are rare and have been found together with ammonites only in the Mt. Camicia section described in this paper. This section permits to correlate the radiolarian assemblages with the ammonite zonation.